Cortical Mechanisms of Single-Pulse Transcranial Magnetic Stimulation in Migraine - Lloyd, Joseph O. (Neurotherapeutics, 2020)
Single-pulse transcranial magnetic stimulation (sTMS) of the occipital cortex is an effective migraine treatment. However, its mechanism of action and cortical effects of sTMS in migraine are yet to be elucidated. Using calcium imaging and GCaMP-expressing mice, sTMS did not depolarise neurons and had no effect on vascular tone. Pre-treatment with sTMS, however, significantly affected some characteristics of the cortical spreading depression (CSD) wave, the correlate of migraine aura. sTMS inhibited spontaneous neuronal firing in the visual cortex in a dose-dependent manner and attenuated l-glutamate-evoked firing, but not in the presence of GABA(A/B) antagonists. In the CSD model, sTMS increased the CSD electrical threshold, but not in the presence of GABA(A/B) antagonists. We first report here that sTMS at intensities similar to those used in the treatment of migraine, unlike traditional sTMS applied in other neurological fields, does not excite cortical neurons but it reduces spontaneous cortical neuronal activity and suppresses the migraine aura biological substrate, potentially by interacting with GABAergic circuits. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-020-00879-6) contains supplementary material, which is available to authorized users.